Infrared and Raman spectroscopy of α‐ZrW2O8: A comprehensive density functional perturbation theory and experimental study. (23rd May 2018) - Weck, Philippe F.; Gordon, Margaret E.; Greathouse, Jeffery A.; Bryan, Charles R.; Meserole, Stephen P.; Rodriguez, Mark A.; Payne, Clay; Kim, Eunja
Abstract: Cubic zirconium tungstate (α‐ZrW2 O8 ), a well‐known negative thermal expansion material, has been investigated within the framework of density functional perturbation theory (DFPT), combined with experimental characterization to assess and validate computational results. Using combined Fourier transform infrared measurements and DFPT calculations, new and extensive assignments were made for the far‐infrared (<400 cm −1 ) spectrum of α‐ZrW2 O8 . A systematic comparison of DFPT‐simulated infrared, Raman, and phonon density‐of‐state spectra with Fourier transform far‐/mid‐infrared and Raman data collected in this study, as well as with available inelastic neutron scattering measurements, shows the superior accuracy of the PBEsol exchange‐correlation functional over standard PBE calculations for studying the spectroscopic properties of this material. Abstract : Cubic zirconium tungstate (α‐ZrW2 O8 ), a well‐known negative thermal expansion material, has been investigated within the framework of PBEsol and PBE density functional perturbation theory, combined with experimental characterization.